The third bullet : a Bob Lee Swagger novel - Hunter, Stephen, 1946- (Hunter, Stephen, 1946- Bob Lee Swagger novel., 2013)
A reimagining of the events surrounding the 1963 assassination of John F. Kennedy finds Bob Lee Swagger drawing on old records, intelligence archives, and observations at the infamous site to investigate a new clue about a third bullet that mysteriously exploded.